Noise-sustained synchronization in a FitzHugh-Nagumo ring with electrical phase-repulsive coupling - dell'Erba, Matias German (2014)
We study the dynamical response under local noise of an excitable ring of FitzHugh-Nagumo units coupled through nearest-neighbor phase-repulsive electric synapses. The system is externally, adiabatically driven by a weak subthreshold periodic signal and independent Gaussian white noises. By varying the coupling strength and the noise intensity, two routes to noise-sustained synchronization are numerically observed and elucidated in terms of the system?s non-equilibrium potential. In particular, the threshold noise intensity for synchronization is theoretically predicted and numerically confirmed.